187 Use of Quantitative Pupillometry in Mild Traumatic Brain Injury to Diagnose and Predict Symptom Severity. (April 2023) - Meister, Melissa; Aderman, Michael; Hershaw, Jamie; Ross, Jeremy; Roach, Megan; Malvasi, Steven; Cameron, Kenneth; Dengler, Bradley
Abstract : INTRODUCTION: Concussion screening using the Military Acute Concussion Evaluation (MACE 2) and imaging modalities can be subjective, time intensive, and monopolize scarce resources in a forward deployed environment. The Pupillary light reflex (PLR) has shown recent promise in identifying mild traumatic brain injuries. METHODS: Freshman entering a military service academy had baseline PLR measurements (starting pupillary diameter, ending pupillary diameter, average constriction velocity, average dilation velocity, constriction latency, constriction percentage, T75 and pupillary wave form) completed using a Neuroptic PLR-3000. If a subject experienced a concussion they returned for PLR measurements and Sport Concussion Assessment Tool (SCAT) scores within 48 hours of injury. RESULTS: Five hundred and fourteen cadets (383 males and 131 females) completed baseline PLR measurements. Sixteen cadets subsequently sustained an mTBI and performed full post-injury assessments. The one-way MANCOVA performed on PLR metrics controlling for symptom severity revealed a marginally significant difference in combined PLR metrics between baseline and post-injury time points [Wilks' λ = .578, F(8, 22) = 2.01, p = .094, partial η = .422]. A significant difference in outcomes between baseline and post-injury were observed for starting pupillary diameter [F(1, 29) = 3.10, p = .089, partial η 2 = .097], average constriction velocity [F(1, 29) = 5.79, p = .023, partial η 2 = .167], and maximum constriction velocity [F(1, 29) = 4.54, p =.042, partial η 2 = .135]. Correlation coefficients demonstrated that post-injury changes in pupillary metrics were strongly associated with post-injury changes in symptom severity, particularly for starting pupillary diameter, constriction percentage, average constriction velocity, maximum constriction velocity, and T75. CONCLUSIONS: In this evaluation of service academy cadets there are measurable differences in pupillary dynamics after sustaining an mTBI which correlates with symptom severity.